Generalist feeding strategies in Arctic freshwater fish: A mechanism for dealing with extreme environments. Issue 3 (8th January 2018) - Laske, Sarah M.; Rosenberger, Amanda E.; Wipfli, Mark S.; Zimmerman, Christian E.
Abstract: Generalist feeding strategies are favoured in stressful or variable environments where flexibility in ecological traits is beneficial. Species that feed across multiple habitat types and trophic levels may impart stability on food webs through the use of readily available, alternative energy pools. In lakes, generalist fish species may take advantage of spatially and temporally variable prey by consuming both benthic and pelagic prey to meet their energy demands. Using stomach content and stable isotope analyses, we examined the feeding habits of fish species in Alaska's Arctic Coastal Plain (ACP) lakes to determine the prevalence of generalist feeding strategies as a mechanism for persistence in extreme environments (e.g. low productivity, extreme cold and short growing season). Generalist and flexible feeding strategies were evident in five common fish species. Fish fed on benthic and pelagic (or nektonic) prey and across trophic levels. Three species were clearly omnivorous, feeding on fish and their shared invertebrate prey. Dietary differences based on stomach content analysis often exceeded 70%, and overlap in dietary niches based on shared isotopic space varied from zero to 40%. Metrics of community‐wide trophic structure varied with the number and identity of species involved and on the dietary overlap and niche size of individual fishes. Accumulation of energy from shared carbon sources by Arctic fishes creates redundancy in food webs, increasing likely resistance to perturbations or stochastic events. Therefore, the generalist and omnivorous feeding strategies employed by ACP fish may maintain energy flow and food web stability in extreme environments.